ANALISIS STRATEGI PEMASARAN MENGGUNAKAN PENDEKATAN MARKETING MIX 7P PADA PT. SIDOMUNCUL BRAND TOLAK ANGIN - Ari Deca Fitriani; Imam Machali (CV. Denasya Smart Publisher, 2026)
This article aims to analyze the sustainable growth strategy of PT. Sidomuncul in a competitive market. The scope of this research is corporate strategy, business competition, and international marketing strategy. The results of the study indicate that PT. Sidomuncul has collaborated with people around them for the marketing stage. The results of the study indicate that PT. Sidomuncul uses a diverse product release strategy. For the Tolak Angin product, it uses the 7P Marketing Mix approach which includes product, price, place, promotion, people, process, and physical evidence. The research method used is descriptive qualitative with data collection techniques through literature studies, documentation, and analysis of various relevant primary sources, such as company reports and related publications. The results of the analysis show that PT. Sidomuncul has implemented an integrated and consistent marketing strategy across all 7P elements. Continuous product innovation, competitive prices, wide distribution, and strong and continuous promotions are able to build the image of Tolak Angin as a trusted modern herbal product. In addition, the support of competent human resources, standardized production processes, and physical evidence in the form of packaging and official certifications also strengthen consumer trust and loyalty. Thus, the implementation of the 7P Marketing Mix for the Tolak Angin brand has proven effective in creating a competitive advantage and maintaining its position as a market leader in the herbal medicine and herbal health product industry in Indonesia.